Alpinia Essential Oils and Their Major Components against Rhodnius nasutus, a Vector of Chagas Disease - Thamiris de A. de Souza; Marcio B. P. Lopes; Aline de S. Ramos; José Luiz P. Ferreira; Jefferson Rocha de A. Silva; Margareth M. C. Queiroz; Kátia G. de Lima Araújo; Ana Claudia F. Amaral (The Scientific World Journal)
Species of the genus Alpinia are widely used by the population and have many described biological activities, including activity against insects. In this paper, we describe the bioactivity of the essential oil of two species of Alpinia genus, A. zerumbet and A. vittata, against Rhodnius nasutus, a vector of Chagas disease. The essential oils of these two species were obtained by hydrodistillation and analyzed by GC-MS. The main constituent of A. zerumbet essential oil (OLALPZER) was terpinen-4-ol, which represented 19.7% of the total components identified. In the essential oil of A. vittata (OLALPVIT) the monoterpene β-pinene (35.3%) was the main constituent. The essential oils and their main constituents were topically applied on R. nasutus fifth-instar nymphs. In the first 10 min of application, OLALPVIT and OLALPZER at 125 μg/mL provoked 73.3% and 83.3% of mortality, respectively. Terpinen-4-ol at 25 μg/mL and β-pinene at 44 μg/mL provoked 100% of mortality. The monitoring of resistant insects showed that both essential oils exhibited antifeedant activity. These results suggest the potential use of A. zerumbet and A. vittata essential oils and their major constituents to control R. nasutus population.